PENGARUH MEDIA FLASH CARD TERHADAP KEMAMPUAN MENGENAL HURUF PADA ANAK KELOMPOK A - Tawaduddin Nawafilaty (Universitas Islam Lamongan, 2017)
The aim of of this study is to know the influence of flash card media on the ability to recognize letters in children of group A children of Al-Kautsar kindergarten Surabaya. This study uses Pre Experimental Design research by using One Group Pretest - Posttest Design model. The subjects used were group A children amounted to 21 children. Data collection methods used are observation and documentation with data analysis technique using Wilcoxon's Signed Rank Test. Based on data analysis obtained by using the Wilcoxon's signed rank test obtained tcount = ttable or 7,4396 = 2,704, and Tcount <Ttabel (0 <59), so Ho is rejected and Ha is accepted. Thus, the study hypothesis that reads